Novel one-step dilute acid-assisted hydrothermal delignification using dilute HNO3 for facile high-purity cellulose extraction from oil palm fronds (OPF) - Ibrahim, Izzudin; Ahmad Farid, Mohammed Abdillah; Andou, Yoshito (Elsevier Ltd, 2025)
Oil palm fronds (OPF), available in abundance, represent a promising sustainable resource, yet its utilization is hindered by the demanding process of cellulose extraction. This study introduces a cost-effective, one-step dilute acid-assisted hydrothermal method using dilute HNO3 (0.5 M) at 120 °C. The selected conditions, with a treatment time of 30 min, resulted in cellulose extraction with a purity of 84.2 wt%, reducing lignin content from 21.8 to 9.3 wt% and hemicellulose from 31.6 to 6.4 wt%. A post-treatment alkaline rinse further increased cellulose purity to 96 wt% and crystallinity to 71.5 %. The method's applicability to other biomasses, including oil palm empty fruit bunch (OPEFB), bamboo, sisal, and shuro palm fibre, showed lignin reduction of up to 85 % and cellulose yields between 78 and 85 %. Thermal stability analysis via TGA indicated a decomposition temperature of 350 °C, and XRD analysis showed a crystallinity index increase from 45 to 62 %. This facile and sustainable process, using only HNO3 and water, marks a significant step forward in biomass valorization, providing environmental benefits by minimizing chemical use for industrial-scale lignocellulosic waste utilization.